Use of ChatGPT as a Decision Support Tool in Human Resource Management - Muhammad Subhan Iswahyudi; Nofirman Nofirman; I Ketut Adi Wirayasa; Suharni Suharni; Ita Soegiarto (Politeknik Ganesha Medan, 2023)
Human Resource Management (HRM) is an important aspect of the success of an organization or company. Effective and efficient HR management can help organizations better achieve their goals and ensure optimal performance from each team member. However, HR management is also faced with various complex challenges, including the management of large teams, diverse needs and expectations of team members, and rapid changes in the business and technological environment. This research aims to investigate the effectiveness and potential use of ChatGPT as a decision-support tool in HR management. This research is a literature review that adopts a qualitative method approach, which means it will analyze and interpret data by relying on information and text from various sources. The study results show that the use of ChatGPT as a decision-support tool in Human Resource Management offers great potential in improving the efficiency, effectiveness, and transparency of HR processes. Artificial intelligence models such as ChatGPT can act as virtual assistants that provide text-based responses, assisting in recruitment, employee development, performance management, and employee support processes. ChatGPT can gather valuable data and insights about employees and the work environment, and help HR managers make more informed decisions.